Geothermal Philately - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1980)
Geothermal energy has been given varying degrees of recognition by countries that are fortunate to possess this natural source of energy. One way in which geothermal, or heat from the earth, is publicized is through postage stamps. These stamps depict natural phenomena such as volcanoes, geysers, hot springs, and fumaroles, as well as man's use of these phenomena in spas, swimming pools, electricity generation, and agriculture. As would be expected, some countries, such as Iceland, have devoted many stamp issues to geothermal energy. Much can be learned from stamps concerning the nature of the resource in the issuing country. The author has made an attempt to identify all of the stamps worldwide relating to geothermal. The Scot's identification number as used in their Standard Postage Stamp Catalog (1980) is given for each stamp. Anyone who is or has been a stamp collector will enjoy a brief tour of the world's geothermal resources